(untitled) (Singapore, 1988)
This purpose was to provide a forum for an updated exchange of information on the status of post harvest technology, to discuss common problems, to shre experience and to make recommendations for action
Keywords: Fisheries research,Fish products,Nghiên cứu nghề cá